2020
DOI: 10.1021/acs.energyfuels.0c02112
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CO2 and Produced Gas Hydrocarbons to Dissolve and Mobilize Bakken Crude Oil at 10.3, 20.7, and 34.5 MPa and 110 °C

Abstract: The ability of an injected gas to dissolve crude oil hydrocarbons may be a major factor controlling the success of enhanced oil recovery (EOR) projects in unconventional reservoirs. Multiple laboratory gas injection tests were conducted using Bakken crude oil in which the gas-dominated upper phase in equilibrium with the bulk crude oil was collected and analyzed to determine dissolved crude oil concentrations and their molecular weight distributions. Dissolved concentrations varied greatly among the test gases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
50
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(54 citation statements)
references
References 54 publications
4
50
0
Order By: Relevance
“…Decreasing solvent strengths were shown by CO 2 and produced gas (which showed similar results) and finally methane, which was a poor hydrocarbon solvent at even the highest pressure. 64 Even though earlier reports have shown the ability of an injected gas to dissolve residual hydrocarbons will be important for successful EOR in unconventional reservoirs, 12,13,44,45,54−57 the factors ultimately controlling oil recoveries will certainly be more complex than can be understood based on experimental MMP and solvent strength data reported for these five candidate injection gases. A variety of additional factors will likely influence oil recoveries including (but not limited to) injected gas penetration into the Bakken rock nanopores, dissolution of the gas into the remaining trapped crude oil, associated oil swelling and reduced viscosity, diffusion of dissolved crude oil hydrocarbons from interstitial pores into the bulk injected gas that dominates fracture spaces, and transport of the gas/oil mixture to production wells.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Decreasing solvent strengths were shown by CO 2 and produced gas (which showed similar results) and finally methane, which was a poor hydrocarbon solvent at even the highest pressure. 64 Even though earlier reports have shown the ability of an injected gas to dissolve residual hydrocarbons will be important for successful EOR in unconventional reservoirs, 12,13,44,45,54−57 the factors ultimately controlling oil recoveries will certainly be more complex than can be understood based on experimental MMP and solvent strength data reported for these five candidate injection gases. A variety of additional factors will likely influence oil recoveries including (but not limited to) injected gas penetration into the Bakken rock nanopores, dissolution of the gas into the remaining trapped crude oil, associated oil swelling and reduced viscosity, diffusion of dissolved crude oil hydrocarbons from interstitial pores into the bulk injected gas that dominates fracture spaces, and transport of the gas/oil mixture to production wells.…”
Section: Introductionmentioning
confidence: 98%
“…62,63 A recent experimental study reported the ability of CO 2 , methane, ethane, propane, and produced gas to dissolve crude oil hydrocarbons at reservoir pressures and temperatures relevant to the Bakken System and showed that Bakken crude oil solvation is (as might be expected) inversely related to the individual gases' MMP values with the same crude oil sample. 46,64 Gases with low crude oil MMPs (e.g., propane and ethane) were superior solvents for crude oil hydrocarbons, while gases with high crude oil MMPs (e.g., methane) showed very poor ability to dissolve crude oil hydrocarbons, especially the heavier hydrocarbons. 64 Propane dissolved the most total oil and the highest fractions of heavier hydrocarbons (e.g., C20− C36) at pressures from 10.3 and 34.5 MPa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors' analysis of the mineralogical composition of the samples indicated that these parameters were not relevant for predicting the recovery factor. In a later study, Hawthorne and Miller [8] investigated the impacts of the injection of various gases under different pressures on the produced hydrocarbon. CO 2 , produced gas (natural gas), and several pure hydrocarbons were tested as potential EOR injections.…”
Section: Introductionmentioning
confidence: 99%
“…In conventional systems, CO 2 penetrates the matrix and causes swelling, viscosity reduction or sweeping of the in-place oil [15]. In shales, the concentration gradientdriven diffusion of hydrocarbons from the interstitial pore spaces in the rock to the surface and into the bulk-injected fluid in the fractures is considered to be the main recovery mechanism [7,8,16,17]. The minimum miscibility pressure (MMP) may not be as important in CO 2 -EOR in shales as it is in conventional systems.…”
Section: Introductionmentioning
confidence: 99%